0317 Quantifying Hazardous Occupational Exposures and Injuries in Home Care: Results from the Safe Home Care Survey0317 Quantifying Hazardous Occupational Exposures and Injuries in Home Care: Results from the Safe Home Care Survey. (23rd June 2014) - Quinn, Margaret; Markkanen, Pia; Galligan, Catherine; Sama, Susan; Kriebel, David; Gore, Rebecca; Punnett, Laura; Davis, Letitia; Laramie, Angela; Brouillette, Natalie; Okyere, Daniel; Sun, Chuan
Abstract : Objectives: In countries with ageing populations, home care (HC) aides are among the fastest growing jobs. There are few quantitative studies of HC occupational safety and health (OSH) hazards. The objectives of this study were to quantify a range of OSH exposures and injuries among HC aides and to evaluate the variability across job categories. Method: HC aides were recruited for a survey via agencies that employ aides and schedule their visits with clients and through a labour union of aides employed directly by clients/families. The innovative questionnaire design included detailed questions about the most recent home visits, as well as about the individual aides' OSH experiences. Results: The final population included 1249 HC aides (634 agency-employed, 615 client-employed) contributing information on 3484 HC visits. Among aides, in the past 12 months, 2% had a needlestick or other sharps injury; 7% reported physical aggression and 19% verbal aggression; 11% had a job-related injury resulting in lost work time or need for medical care; 33% reported back pain: of these, 59% experienced pain once a week or more and 68% took medication for it. Among visits, in the past month, 62% involved patient handling while only 25% involved a patient handling device; 80% involved cleaning, 10% indoor cigarette smoke. Agency-employed versus client-employed aides differed by amount of client handling, use of sharps, and characteristics of clients. Conclusions: Aides experience substantial OSH exposures and injuries. Quantification of hazards is useful to prioritise resources for the development of preventive interventions and to provide a foundation for etiologic research.